The Use of a Web-Based Course Management System: Causes and Performance Effects. (December 2013) - Ring, J. Kirk; Kellermanns, Franz W.; Barnett, Tim; Pearson, Allison W.; Pearson, Rodney A.
This article reports the results of two studies that examined (a) students' intentions to use a web-based course management system, (b) their actual use of a course management system, and (c) the effect of their use of a course management system on classroom performance. We found that students' attitudes toward the course management system, perceptions of support, and perceptions of their capacity to control their actions each were associated with their intentions to use the course management system. Subsequently, intentions directly influenced actual use of the course management system and greater usage of the course management system had a statistically significant, albeit modest, positive effect on students' performance in the course. Practical applications of the findings are discussed.